Analyst's ability, media selection and investor interests: evidence from China. Issue 1 (20th February 2017) - Yin, Yugang; Tan, Bin
Abstract : Purpose: The purpose of this paper is to find out whether the election of star analysts leads to the conflict of interests between analysts\institutional investors and individual investors. And then, further investigate how the election results to influence the individual investors' decision making. Design/methodology/approach: Given the fact that earnings forecasts and stock ratings are the most important foundations for the investor's investment decision, the authors investigate the relationship among the earnings forecasts, abnormal returns and the election of star analyst. This paper further analyzes the impact factors on investors' decision. The data used in this paper for star analysts' information, analysts' forecast and recommendations, as well as stock performances-related data are from 2005 to 2012. Findings: This paper finds that mass media cannot select analysts with high forecast accuracy, and then misleads investors. It demonstrates that the analysts with poorer forecast ability and more optimistic stock recommendations are more prone to be entitled as star analysts by mass media, and these titled star analysts tend to show a poorer performance. Therefore, the star analyst worsens investors' cognition on analysts forecast ability and then misleads investors' decision making. Social implications: Media plays a critical role in corporate governance, information collection and diffusion and reducing the information asymmetry, however, it is good to know the role of media in financial markets from a broader perspective. Because media may also bring negative factors to the financial markets such as misguiding the investors and intensify the conflict of interests between analyst and individual investors. Originality/value: This paper supports a new perspective of the role of mass media in financial market, which is different from existing studies.